Implementation of User Experience (UX) Design on Library Website: Implementasi Desain User Experience (UX) pada Website Perpustakaan - Vina Oktaviani, S.Pd., M.T.; Sastrawijaya, Yuliatri; Fauzan , ZE. Ferdi; Tampubolon, Metawani (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
The management of libraries in Indonesia is generally still done manually, leading to several issues such as inaccurate book inventory data and unclear transaction processes. The aim of this research is to design a web-based library information system using the User Experience (UX) concept, which will provide ease of use for users by focusing on effectiveness, efficiency, and satisfaction. This concept involves four stages: analysis, design, implementation, and evaluation. During the analysis stage, data collection is carried out through observation, interviews, and the distribution of questionnaires to understand the needs of the members. Next, the system is designed to meet the needs of both the members and the management. After that, usability testing is conducted to evaluate the effectiveness, efficiency, and user satisfaction with the system. The testing involved 15 members and library staff. The results showed that in terms of effectiveness, all tasks were above the average completion rate. In terms of efficiency, the product usage time was satisfactory, and in terms of satisfaction, using the UEQ (User Experience Questionnaire) showed good to very good results. Therefore, the library system can be used by library members to support their library activities.